PELATIHAN LITERASI DIGITAL : PEMANFAATAN MEDIA CANVA UNTUK PEMBELAJARAN - Muh. Amiruddin Salem; Hasanah Purnamasari; Robi'ah Awaliyah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Digital literacy training using the Canva platform was conducted at MIS Al-Hidayah Leuwohung, involving 13 teachers as participants. This training aims to improve teachers' ability to create interesting and interactive learning materials. The training methods included material presentation, hands-on practice, and Focus Group Discussion (FGD). The results of the training showed that the majority of participants were able to produce designs that meet the criteria of aesthetics, creativity, and learning relevance. Evaluation through questionnaires showed that the training was very useful and relevant to the participants' needs. The obstacles faced, such as limited devices and internet connection, were successfully overcome with appropriate solutions. The positive impact of this training is not only to improve teachers' competence in digital literacy, but also to create a more interesting learning experience for students.